2005
DOI: 10.1136/thx.2005.041475
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence bronchoscopy with white light bronchoscopy compared with white light bronchoscopy alone for the detection of precancerous lesions: a European randomised controlled multicentre trial

Abstract: Background: The potential of autofluorescence bronchoscopy (AFB) to detect precancerous lesions in the central airways and its role in lung cancer screening is uncertain. A study was undertaken to evaluate the prevalence of moderate/severe dysplasia (dysplasia II-III) and carcinoma in situ (CIS) using a newly developed AFB system in comparison with conventional white light bronchoscopy (WLB) alone. Methods: In a prospective randomised multicentre trial, smokers >40 years of age (>20 pack-years) were stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 28 publications
3
117
0
6
Order By: Relevance
“…Among the studies [37][38][39][40][41][42][43][44][45][46][47][48] of AFB versus WLB for detecting cancers and precancerous lesions, most have concluded that AFB has a much higher sensitivity and a lower specificity than WLB. 11,13,40,41 AFI has shown significantly higher sensitivity in almost all the studies to date.…”
Section: Diagnostic Performance Of Afi Versus Wlbmentioning
confidence: 99%
“…Among the studies [37][38][39][40][41][42][43][44][45][46][47][48] of AFB versus WLB for detecting cancers and precancerous lesions, most have concluded that AFB has a much higher sensitivity and a lower specificity than WLB. 11,13,40,41 AFI has shown significantly higher sensitivity in almost all the studies to date.…”
Section: Diagnostic Performance Of Afi Versus Wlbmentioning
confidence: 99%
“…The investigators found that AFB + WLB had a relative sensitivity of 6.3 compared to WLB alone. The specificity of AFB was 66%.Many subsequent literature studies (Level of evidence: III) including varying categories of patients with known/suspected lung cancer, or at high-risk of developing lung cancer, confirmed the superiority of AFB + WLB versus WLB in the detection of dysplasia and CIS, even though the relative sensitivity of AFL + WLB was usually found to be lower than that reported in the 1998 study by Lam et coll [10][11][12][13].More recently, the first prospective, randomised, multicentric study compared WLB + AFB versus WLB in 1173 smokers with additional risk factors for lung cancer (Level of evidence: Ib) [4]. The results of this study confirmed the superiority of AFB over WLB in the detection of preneoplastic and early neoplastic lesions, but did not support the high expectations raised by many previous studies.…”
mentioning
confidence: 58%
“…Second, the relative sensitivity of WLB + AFB versus WLB alone found in this study (1.42) was much lower than in many previous studies, and the superiority of AFB over WLB was statistically significant only for moderate/severe dysplasia and not for CIS. The specificity was 58% for WLB + AFB, and 62% for WLB alone.In conclusion, the experience with AFB accumulated so far suggests that [1,3,4,[10][11][12][13][14]: 1) this method is superior to WLB alone, especially in the detection of preneoplastic lesions (moderate to severe dysplasia); 2) it is quite clear that this depends mainly on the sensitivity of WLB. In those studies where the sensitivity was particularly low [Lam] the relative sensitivity of AFB + WLB versus WLB alone was markedly higher; 3) the prevalence of preneoplastic lesions in the population being studied is extremely important, and it has proved highly variable in studies into AFB published thus far.…”
mentioning
confidence: 99%
“…BIB ve OFB'de patoloji saptanmayan bölgeler biyopsisiz gerçek negatif kabul edilmiştir. Bir çalışmada rastgele alınan biyopsilerin ekonomik maliyeti artırdığı ve BIB + OFB'nin bu biyopsiler alınmadan daha efektif olabileceği bildirilmiştir (15).…”
Section: Discussionunclassified